Tax compliance cost of bumiputera small and medium enterprises in Northern Malaysia - Abdul Mansor, Hafizah; Mohd Hanefah, Mustafa (Universiti Utara Malaysia, 2008)
This paper explores and measures the level of tax compliance costs among Bumiputera small and medium enterprises in the Northern Region of Malaysia for the year of assessment 2003. The findings revealed that the tax compliance costs have a significant relationship with the paid up capital(size of enterprises). Overall, the tax compliance cost of Bumiputera small and medium enterprises was RM880,110 for the assessment year 2003. Furthermore tax compliance cost of smaller Bumiputera enterprises amounted to RM413,670 while the larger Bumiputera enterprises was RM466,440.The average tax compliance cost is RM22,003. Most of the large Bumiputera enterprises incurred more external tax compliance costs than internal compliance costs (62.34%) compared to the smaller Bumiputera enterprises (37.66%). In contrast, the smaller Bumiputera enterprises incurred more internal tax compliance costs of about 83% as compared to external tax compliance costs (17%). The results also indicated that small Bumiputera enterprises have a higher percentage of tax compliance costs based on tax revenue, which is 2.57 times more compared to large Bumiputera enterprises,which amounted to only 0.46 times.